The return to work after sick leave due to common mental disorders among young employees: a qualitative interview study with young employees and managers - Caroline Olsson; Irene Jensen; Lotta Nybergh; Elisabeth Björk Brämberg; Helena Tinnerholm Ljungberg (BMC Public Health)
Abstract Background Studies focusing on the return for young employees are scarce. The aim of this study was to investigate the return to work process after a period of sick leave due to common mental disorders among young male and female employees, with a specific focus on promoting and hindering factors. A gender perspective was applied to examine potential patterns of similarities and differences in the study participants’ experiences. Methods A qualitative approach with an applied gender perspective was used to capture both young employees’ and managers’ experiences of the return to work process. The data consisted of interviews with 12 young male and 13 young female employees (aged 20–29) and 23 interviews with managers with experience of supervising at least one young employee during return to work. An inductive, conventional content analysis was conducted. Results The analysis resulted in three main categories and five subcategories describing hindering and promoting factors in young employees’ return to work processes. The main and subcategories were (1) “Coordinating, planning, and timing the return to work process” (with subcategories “Lack of coordination and support from key stakeholders”, “The importance of a return to work plan and follow-up”, and “The timing of the return to work”); (2) “Gaining sufficient support and having personal resources” (with subcategories: “Level and quality of support in the work environment”, and “Resources and obstacles on a personal level”); and (3) “Poor match between the young employees’ capabilities and the work demands or working conditions”. Conclusion The study participants identified similar factors that promoted and hindered the return to work process. Young employees need more support from employers and various welfare agencies. Managers need to know more about the return to work process and the responsibility of involved stakeholders. No expressed gender differences were identified.